2021
DOI: 10.1007/s12155-021-10329-6
|View full text |Cite
|
Sign up to set email alerts
|

Fungal pretreatment of sugarcane bagasse: a green pathway to improve saccharification and ethanol production

Abstract: Biological pretreatment was investigated to increase ethanol production from lignocellulosic biomass, like sugarcane bagasse. Enzyme secretion, changes in substrate composition, enzymatic hydrolysis and ethanol yield after pretreatment by different basidiomycetes were evaluated. Analysis by Fourier transform infrared spectroscopy showed that P. pulmonarius PS2001 and T. villosa 82I6 promoted more extensive selective modi cations in the lignin content. Glucose release during enzymatic hydrolysis of samples pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The treatment of rice straw with 10 IU/g enzyme (CMCase) at 30,40 and 50 ºC temperature for 24 and 48 h on rotatory shaker revealed that Penicillium chrysogenum released highest amount of reducing sugar followed by Aspergillus flavus, A. oryzae, A. fumigatus and Trichoderma viride (Table 1). The release of reducing sugars further increased with increasing temperature and duration of incubation that suggest that the enzyme complex released by the microfungi is not de-activated on longer periods of incubation and increasing temperature [35,36,37]. Further the experiments were designed to evaluate the degradation potential of Penicillium chrysogenum, Aspergillus flavus and A. oryzae singly and in combination of each other under field conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of rice straw with 10 IU/g enzyme (CMCase) at 30,40 and 50 ºC temperature for 24 and 48 h on rotatory shaker revealed that Penicillium chrysogenum released highest amount of reducing sugar followed by Aspergillus flavus, A. oryzae, A. fumigatus and Trichoderma viride (Table 1). The release of reducing sugars further increased with increasing temperature and duration of incubation that suggest that the enzyme complex released by the microfungi is not de-activated on longer periods of incubation and increasing temperature [35,36,37]. Further the experiments were designed to evaluate the degradation potential of Penicillium chrysogenum, Aspergillus flavus and A. oryzae singly and in combination of each other under field conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To date, few studies evaluating the biological pretreatment of SCB have been reported [84]. However, some studies have shown that the use of fungi enhances the digestibility of polysaccharides, while very few microorganisms are able to fully decompose lignin in SCB [115][116][117]. Microbial consortium pretreatment has been used on lignocellulosic biomass to increase biogas production [118,119].…”
Section: Pretreatment Of Sugarcane Bagassementioning
confidence: 99%